2013
DOI: 10.3390/su5083543
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of the Capability Assessment Tool for Sustainable Manufacturing

Abstract: This paper explores the performance of a novel capability assessment tool, developed to identify capability gaps and associated training and development requirements across the supply chain for environmentally-sustainable manufacturing. The tool was developed to assess 170 capabilities that have been clustered with respect to key areas of concern such as managing energy, water, material resources, carbon emissions and waste as well as environmental management practices for sustainability. Two independent exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…To do this, the expert team defined a qualitative strategy map. For each perspective, critical success factors and their relationships were identified according to the team of experts and literature review [50][51][52][53]. Details are shown in Figure 3.…”
Section: Phase#1: As Is Analysismentioning
confidence: 99%
“…To do this, the expert team defined a qualitative strategy map. For each perspective, critical success factors and their relationships were identified according to the team of experts and literature review [50][51][52][53]. Details are shown in Figure 3.…”
Section: Phase#1: As Is Analysismentioning
confidence: 99%
“…They have rapidly become the fundamentals for decision making progressions in many organizations, but also have often failed to deliver their expected benefits (Basu & Lederer, 2011), (Ghosh, 2012), (Reş, 2011), (Xue, Liang, Boulton, & Snyder, 2005), (Bresfelean, Bresfelean, Ghisoiu & Comes, 2006), (Ward, Daniel, & Peppard, 2008), (Subic, Shabani, Hedayati, & Crossin, 2013). A new ERP solution is of crucial importance for a company's future (at least in the next decade of subsistence) due to its all-encompassing character (Holland & Light, 1999): it automates core corporate activities (manufacturing, human resource, finance, supply chain management), incorporates top practices to assist rapid decision-making processes, cost diminution, and superior management control.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 90's, studies showed that ERP implementations success rate was less than 40% and the great majority were behind schedule or exceeded the funds (Xue, Liang, Boulton, & Snyder, 2005), (Ward, Daniel, & Peppard, 2008), possibly due to poor cost and schedule estimations or changes in project scope rather than project management failure. Even in recent years (Eckartz, Daneva, Wieringa, & van Hillegersberg, 2009), (Subic, Shabani, Hedayati, & Crossin, 2013) after costly IT investments, numerous companies (65% from a case study sample) complained about their business cases that failed to identify and manage benefits in the deployment processes. Furthermore, 70% of ERP implementations proved to be unsuccessful (Al-Mashari, 2006) mainly due to (Eckartz, Daneva, Wieringa, & van Hillegersberg, 2009): business strategies, project delays, cost overruns and underestimation of the effort required for winning managerial changes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GCSM plays a vital role in the improvement and implementation of a firm's competitive advantages [28,29]. When selecting supply chain partners, firms evaluate the social and environmental responsibilities of suppliers using publicly available information, self-assessment questionnaires, review of other non-proprietary information, develop of assessment tools, and on-site audits [14,30]. Environmental on-site audits allow for a deep and broad understanding of the supplier's capabilities and activities but remain costly.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%